Wildlife toxicity assessments for chemicals of military concern - Williams, Marc A. (Biologist); Reddy, Gunda; Quinn, Michael J.; Johnson, Mark S.; ScienceDirect eBooks (Amsterdam, The Netherlands : Elsevier, 2015)
Wildlife Toxicity Assessments for Chemicals of Military Concern is a compendium of chemical-specific toxicity information with discussions on the rationale and development of Wildlife Toxicity Reference Values (TRVs) intended for use on terrestrial wildlife for risk assessment applications. Substances covered include military-related chemicals including explosives, propellants, pesticides and metals. Wildlife Toxicity Assessments for Chemicals of Military Concern is a much-needed resource designed to meet the needs of those seeking toxicological information for ecological risk assessment p.
Avian Oral Toxicity: AcuteAvian Oral Toxicity: Subacute; Avian Oral Toxicity: Subchronic; Avian Oral Toxicity: Chronic; Avian Oral Toxicity: Other; Studies Relevant for Avian TRV Development: RDX Ingestion Exposures; Avian Inhalation Toxicity; Avian Dermal Toxicity; Amphibian Toxicology; Reptilian Toxicology; Recommended toxicity reference values; Toxicity Reference Values for Mammals; TRVs for Ingestion Exposures for the Class Mammalia; TRVs for Inhalation Exposures for the Class Mammalia; TRVs for Dermal Exposures for the Class Mammalia; Toxicity Reference Values for Birds.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Environmental toxicology; Toxicity testing; Chemical weapons -- Testing; SCIENCE -- Life Sciences -- Anatomy & Physiology; Chemical weapons -- Testing; Environmental toxicology; Toxicity testing; Environmental Pollutants -- toxicity; Animals, Wild; Environmental Pollution -- adverse effects; Electronic books